The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1039/d3cp05557d
|View full text |Cite
|
Sign up to set email alerts
|

Economical quasi-Newton unitary optimization of electronic orbitals

Samuel A. Slattery,
Kshitijkumar A. Surjuse,
Charles C. Peterson
et al.

Abstract: We present an efficient quasi-Newton orbital solver optimized to reduce the number of gradient evaluations and other computational steps of comparable cost. The solver optimizes orthogonal orbitals by sequences of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 112 publications
(299 reference statements)
0
0
0
Order By: Relevance
“…Although the near-zero gap displayed for 1FUL in section is typical for zwitterions in vacuum, we have found that for a different zwitterion our local SCF solver is able to converge to the “physically correct” charge-separated solution. In Figure we display the HOMO and LUMO for 1RVS when the QUOTR solver is given the usual extended-Hückel-like initial guess for the orbitals, but without perturbation . We see that there is no unphysical mixing of the occupied orbital on the CO 2 – with the unoccupied orbital on the NH 3 + .…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Although the near-zero gap displayed for 1FUL in section is typical for zwitterions in vacuum, we have found that for a different zwitterion our local SCF solver is able to converge to the “physically correct” charge-separated solution. In Figure we display the HOMO and LUMO for 1RVS when the QUOTR solver is given the usual extended-Hückel-like initial guess for the orbitals, but without perturbation . We see that there is no unphysical mixing of the occupied orbital on the CO 2 – with the unoccupied orbital on the NH 3 + .…”
Section: Resultsmentioning
confidence: 97%
“… a The standard (RH) SCF solver values are from ref , whereas the quasi-Newton (QUOTR) SCF solver values are from this work. For all cases where the standard solver failed to converge to a solution, the quasi-Newton solver located a solution with a vanishing HOMO–LUMO gap. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations